Factors affecting the local distribution of the Long-tailed Duck Clangula hyemalis in Baltic offshore waters - Nilsson, Leif; Ogonowski, Martin; Staveley, Thomas A.B. (Wildfowl, 2016)
The Long-tailed Duck Clangula hyemalis is the main offshore wintering seaduck species in the Baltic region, although numbers have declined steeply since the early 1990s. The reasons for the decline are not well understood and information about habitat choice is scarce. Blue Mussels Mytilus edulis are the main food source for Long-tailed Ducks in the southern Baltic Sea and here we have used both modelled and measured raw data on Mytilus abundances, patchiness and various bathymetric parameters to study Long-tailed Duck habitat preferences. Long-tailed Ducks were most abundant at depths of 10–30 m and in areas of high Mytilus densities. Patchiness of the resource was also very influential, especially when overall Mytilus densities were low. Bird abundance was intermediate to high in areas of low patchiness and low where Mytilus patchiness was high. This suggests that the birds seek areas that optimise their feeding efficiency.